Combinatorial epigenetic deregulation by Helicobacter pylori and Epstein–Barr virus infections in gastric tumourigenesis. Issue 3 (20th May 2016) - Wu, William KK; Yu, Jun; Chan, Matthew TV; To, Ka F; Cheng, Alfred SL
Abstract: Epigenetic mechanisms, including DNA methylation, histone modifications, chromatin remodelling and microRNAs, convert environmental signals to transcriptional outputs but are commonly hijacked by pathogenic microorganisms. Recent advances in cancer epigenomics have shed new light on the importance of epigenetic deregulation in Helicobacter pylori ‐ and Epstein–Barr virus (EBV)‐driven gastric tumourigenesis. Moreover, it is becoming apparent that epigenetic mechanisms interact through crosstalk and feedback loops, which modify global gene expression patterns. The SWI/SNF remodelling complexes are commonly involved in gastric cancers associated with H. pylori or EBV through different mechanisms, including microRNA‐mediated deregulation and genetic mutations. While H. pylori causes epigenetic silencing of tumour‐suppressor genes to deregulate cellular pathways, EBV‐positive tumours exhibit a widespread and distinctive DNA hypermethylation profile. Given the early successes of epigenetic drugs in haematological malignancies, further studies are mandated to enrich and translate our understanding of combinatorial epigenetic deregulation in gastric cancers into interventional strategies in the clinic. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.